Survival benefits of adjuvant chemotherapy after conversion surgery in patients with advanced pancreatic cancer - Yoon Suk Lee; Jang Won Lee; Hak Jun Kim; Jung Won Chun; Jong-Chan Lee; Dong Kee Jang; Jin-Hyeok Hwang; Young Ae Kim; Sang Myung Woo (Frontiers in Oncology)
BackgroundOncologic outcomes of conversion surgery for advanced pancreatic cancer (PC) have scarcely been reported. Therefore, this study aimed to investigate the outcomes of conversion surgery with preoperative treatment of FOLFIRINOX or gemcitabine with nab-paclitaxel (GnP) for patients with advanced PC including locally advanced or metastatic PC.MethodsUsing the National Health Insurance database between 2005 and 2020, we identified patients who underwent conversion surgery after chemotherapy with FOLFIRINOX or GnP for advanced PC. The patients were categorized based on preoperative treatment. Survival outcomes were evaluated based on the date of cancer diagnosis and conversion surgery.ResultsAmong 69,183 patients with advanced PC, 476 underwent conversion surgery; 430 with FOLFIRINOX and 46 with GnP. The median duration from diagnosis to conversion surgery was 6.4 months. Overall survival (OS) was 31.2 months after cancer diagnosis and 23.5 months after conversion surgery. Adjuvant chemotherapy was a significant factor for OS, with hazard ratios (HRs) of 0.23 [95% CI 0.12–0.44, P < 0.01] from cancer diagnosis and 0.20 [95% CI 0.10–0.37, P < 0.01] from conversion surgery. No significant differences were noted between FOLFIRINOX and GnP. However, maintaining the same regimens as preoperative chemotherapy was a significant factor, with HRs of 0.67 [95% CI 0.47–0.95, P = 0.02] from cancer diagnosis and 0.69 [95% CI 0.49–0.98, P = 0.04] from conversion surgery.ConclusionsThe incorporation of adjuvant chemotherapy with the same preoperative regimen could be an effective strategy for patients with advanced PC who would undergo conversion surgery.